Pagdadalaga at pagbibinata : developmental contexts of adolescent sexuality - Ujano-Batangan, Maria Theresa D. (Quezon City, Philippines : University Center for Women's Studies, University of the Philippines, 2006)
This article looks at previous research that showed various developmental factors related with adolescent sexuality.
1. The period of adolescence -- 2. Development of self in adolescence -- 3. Adolescent Relationship -- 4. Adolescent Sexuality -- 5. Summary and implications.
"A comprehensive capacity development project for integrating reproductive health and rights principles into sexuality education curricula and training/advocacy designs."
Includes bibliographical references.
Keywords: ADOLECENCE -- PHILIPPINES